Repressed Memories as a Coping Mechanism: The Impact of Childhood Sexual Abuse Growth in The Perks of Being a Wallflower - Beth Icalavida Unggul Dalih; Ruly Indra Darmawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This article explores the repressed memories as a coping mechanism in Stephen Chbosky’s The Perks of Being a Wallflower, focusing on how the trauma of childhood sexual abuse impacts the victim’s psychological growth. Through using the Lacanian’s lens of the Real, the Symbolic, and the Imaginary (RSI), this research analyses how the trauma that is pushed into the Real, only resurface through behavioral triggers. The main character in this book, Charlie, as a subject represents a teenager whose a victim of childhood sexual abuse by his Aunt trying to repress his trauma by making a good idealize and reading book as his coping mechanism due to prevent psychic collapse. By analyzing Charlie’s mental breakdown, the study discovers that the return of Charlie’s hidden trauma is the key to his recovery psychology and  personal growth. The transition from being an observer into a person who feels whole, allowing him to achieve self-acceptance and sense of inner peace through friendship.